Flavan-Containing Cells Delimit Frankia-Infected Compartments in Casuarina glauca Nodules - Laplaze, Laurent (American Society of Plant Physiologists, 1999)
We investigated the involvement of polyphenols in the Casuarina glauca-Frankia symbiosis. Histological analysis revealed a cell-specific accumulation of phenolics in C. glauca nodule lobes, creating a compartmentation in the cortex. Histochemical and biochemical analyses indicated that these phenolic compounds belong to the flavan class of flavonoids. We show that the same compounds were synthesized in nodules and uninfected roots. However, the amount of each flavan was dramatically increased in nodules compared with uninfected roots. The use of in situ hybridization established that chalcone synthase transcripts accumulate in flavan-containing cells at the apex of the nodule lobe. Our findings are discussed in view of the possible role of flavans in plant-microbe interactions.